Motif Menonton Video For Your Page Tiktok dan Kepuasaan Hiburan pada Siswa SMA PGRI Pekanbaru - Nurhajimah Sukma; Suyanto Suyanto (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
In the current era of globalization, there are many applications that make it easier for users to get satisfaction, one of which is the Tiktok application. With the tiktok application, many people, not only adults, but also children and teenagers can see information or news that encourages them to watch For Your Page (FYP) on Tiktok. So that teenagers or adults are motivated and feel satisfied because of the For Your Page (FYP) on Tiktok. Based on the phenomenon above, this study aims to determine how much influence the motive for watching For Your Page (FYP) TikTok has on entertainment satisfaction in SMA PGRI Pekanbaru students. The theory used is the Uses and Gratification Theory which is a theory of needs and satisfaction in which audiences use the media in order to fulfill their needs. What is assumed is that the audience is considered active, can change the satisfaction of needs, the mass media competes with other media. This study uses a quantitative method with a descriptive approach. Data collection techniques used are questionnaires and documentation. How to distribute the questionnaire is done by going down directly to SMA PGRI and online via Google from. The population in this study were 153 students. The sampling technique used in this study is the Non-Probability Sampling Technique. Using Saturated Sampling in which the entire population is sampled. To find out how much influence these two variables have. For processing questionnaire data, it was carried out using the Product And Service Solution (SPSS) statistical program26. Based on these results it shows that the influence of motives for watching For Your Page TiktTok on Entertainment Satisfaction in SMA PGRI Pekanbaru students. The regression coefficient value obtained in this study is Y = 4.023 +0.878X, a significance level of 0.000, which is smaller than α = 0.05, meaning that there is an influence between Motives for Watching FYP TikTok on entertainment satisfaction in SMA PGRI Pekanbaru students of 74.2% and in category of strong influence (60% -79.99%).